(untitled) (Journal of humanities and social sciences exploratio, 2025)
This article systematically analyzes the key characteristics of the new-economy boom and the deep-seated challenges it poses for the rule-of-law system, covering dimensions such as innovation-driven growth, digital virtualization, cross-sector integration and platform collaboration. Drawing on four perspectives—legislation, law enforcement, the judiciary and legal culture—it proposes a road-map for building an agile, scientific, collaborative and intelligent modern legal ecosystem, with the goal of providing institutional guarantees for the healthy development of the new economy and offering practical insights for the modernization of the rule of law in China.